Constraints related to developing small-scale PPPs and how to reduce them. Issue 1 (4th January 2017) - Thierie, Wouter; De Moor, Lieven
Abstract : Purpose: The purpose of this paper is to better understand the constraints related to developing small-scale public-private partnerships (PPPs) and how to reduce them. Design/methodology/approach: The paper provides a general review of the characteristics of small-scale PPPs and identifies overarching concerns. Findings: The paper finds for small-scale PPPs constraints with respect to the definition, government processes and procedures, transaction costs, public capacity and institutional structure; important issues of transaction costs, minimum size requirement and increasing popularity and recommendations for further development. Practical implications: Since most small PPPs are conducted by cities and regional governments, many local bodies would benefit from a better understanding of small-scale projects, helping to develop standard documentation, which is especially relevant for small-scale projects given their relatively large transaction and bid costs, supporting the long-term growth of small PPPs. Originality/value: Small-scale PPPs have different characteristics compared with large projects and these characteristics should be studied separately. Although the benefits of small-scale projects are undeniable, relatively few have been undertaken relative to the substantial requirement. A more thorough understanding of the constraints related to developing small-scale PPPs and how to reduce them would help the subset of small projects to reach its full potential. This paper serves as a first step, clearing the ground for further research in specific areas.